2009
DOI: 10.3324/haematol.2009.006916
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcome of patients older than 30 years receiving HLA-identical sibling hematopoietic stem cell transplantation for severe acquired aplastic anemia using fludarabine-based conditioning: a comparison with conventional conditioning regimen

Abstract: Older age is a limitation for HLA-identical sibling hematopoietic stem cell transplantation (HSCT) as first-line therapy for severe acquired idiopathic aplastic anemia (SAA). Fludarabine (Flu)-based conditioning might improve outcome in older patients. We analyzed retrospectively 30 patients older than 30 years receiving such reduced-intensity conditioning HSCT according to recommendations of the European Group for Blood and Marrow Transplantation (EBMT) and compared their outcome to a control group receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 20 publications
3
78
0
1
Order By: Relevance
“…The OS was also better. 15 In a phase II prospective study, no GF was found in 28 patients with SAA who received Flu/CY/ATG conditioning regimen. 16 BU is an alkylating agent with low immunosuppressive activity.…”
Section: Discussionmentioning
confidence: 99%
“…The OS was also better. 15 In a phase II prospective study, no GF was found in 28 patients with SAA who received Flu/CY/ATG conditioning regimen. 16 BU is an alkylating agent with low immunosuppressive activity.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, suggest that UD allo-HSCT should be safely considered up to 30 years of age, approaching the clinically relevant age cut off of 40 years in the setting of HLA-identical sibling allo-HSCT. 22,23 For older patients, UD allo-HSCT should be performed with caution in highly selected patients, especially in the presence of additional poor risk factors such as comorbidities. 5 Regarding the timing of allo-HSCT, we found better OS when allo-HSCT was performed earlier, within the first year following diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Flu-based preconditioning regimen is widely used in HSCT for SAA from MSD or alternative donors. [14][15][16] In such situations, low-dose TBI is usually combined with chemotherapeutic agents to avoid rejection in Japan. Adverse effects of radiation include not only LM but also endocrinological disorders, such as hypothyroidism or hypogonadism, or other organ dysfunctions.…”
Section: Discussionmentioning
confidence: 99%